OPTIMASI CAMPURAN AVICEL PH 101 DAN LAKTOSA SEBAGAI BAHAN PENGISI PADA TABLET EKSTRAK BUNGA ROSELLA (Hibiscus sabdariffa L.) SECARA GRANULASI BASAH - Kokafrinsia, Zila Tjhia; Saryanti, Dwi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Rosella flower (Hibiscuss sabdariffa L.) in traditional medicine can provide protection against various diseases, such as coronary heart disease, cancer, lowering cholesterol, and liver disorders. This study aims to obtain the optimum formula of tablet of rosella flower extract with a mixture of Avicel PH 101 and lactose as a filler using wet granulation method. Rosella flower extract was obtained by maceration of rosella flower powder using 70% ethanol. The optimization formula for tablets using the Simplex Lattice Design method with Design Expert software version 10. The parameters used in the optimization are weight variation, hardness, friability and disintegration time. Verification of the optimal formula using the SPSS 18 program with the One Sample T-test method with a confidence level of 95%. The results showed that the optimal formula of tablet of rosella flower extract was the Avicel PH 101 97.82%: 2.17% lactose. The optimal formula has weight variation 1.53% ± 0.0073; hardness 5.087 kg ± 0.5135; the friability is 0.3% ± 0.041. The resulting disintegration was 22.99 minutes ± 2.218. The results of the verification of the optimal formula show that there is no significant difference between the predictions of the Simplex Lattice Design method and the results of the tests performed so that it can be said that the method is valid.